Автобіографічні риси романів Латіфе Текін - Лавров, Д.В. (Культура народов Причерноморья, 2013)
Дана стаття присвячення дослідженню творчості Латіфе Текін через призму
автобіографічного минулого авторки. Читач має можливість ознайомитися з головними творами
Латіфе Текін, яка є однією з найвідоміших і найперших постмодерністок на теренах сучасної
Туреччини, і простежити, яким чином елементи з минулого письменниці відображаються у житті,
побуті, характері та світобаченні головних героїв її романів. Стаття є показовою для розуміння та
сприйняття творчості Латіфе Текін, як представниці потужної течії турецького постмодернізму. Данная статья посвящения исследованию творчества Латифе Текин через призму
автобиографического прошлого автора. Читатель имеет возможность ознакомиться с главными
произведениями Латифе Текин, которая является одной из самых известных и первых
постмодернисток на территории современной Турции, и проследить, каким образом события из
прошлого писательницы отражаются в жизни, быту, характере и мировоззрении главных героев ее
романов. Статья показательна для понимания и восприятия творчества Латифе Текин, как
представительницы мощного течения турецкого постмодернизма. This article is devoted to the autobiographical features in the novels of Latife Tekin. The reader has a
possibility to become familiar with the works by Latife Tekin, who is one of the most famous and earliest
postmodernist writers on the territory of modern Turkey. Now we can trace the process of the elements from the
author`s past appearance in life and outlook of the main characters of Tekin`s novels. This article is
demonstrative for the understanding and perception of Latife Tekin`s creativity as a powerful representative of
the current Turkish postmodernism.
According to Latife Tekin, all the books she wrote are autobiographical, direct confirmation to her thesis can be
found in every of her well-known works, because it would be quite inaccurate to identify features of
autobiographical writing in some parts of her novels neglecting the whole picture, that is to be seen through
the prism of reader`s perception.
The main aim of Latife Tekin`s hybrid confluence of creativity and recollection is to represent the real, live,
perceptible pictures from the life of Turkish society on the example of low-income groups. The author chooses
the life in slums to get the real picture of the human`s nature, when extremely limited in modern life
accommodations main characters, show the real nature of human being and world`s perception. As the result,
Latife Tekin while creating the novels remembering far past from her childhood, tries to make us understand,
that our thoughts, way of life, world seeing is quite subjective and the best way to get acquainted with the life of
others is to feel this life. That is why from the one hand we can consider that Latife Tekin`s novels are
autobiographical and from the other – they are natural and highly related to a real life.